2014
DOI: 10.7314/apjcp.2014.15.19.8047
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Essential Oils: Targeting of Protein Networks in Cancer Cells

Abstract: Cancer is a multifaceted and genomically complex disease and research over decades has gradually and sequentially shown that essential biological mechanisms including cell cycle arrest and apoptosis are deregulated. We would give an overview of newly emerging experimental evidence addressing different molecular mechanisms reported to be regulated by these phytochemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Owing to the possession of antibacterial and anti-cancer activities, plant essential oil has become the focus of phytomedicine research 40 , 41 and drug delivery system formulation development. 42 In recent times, lavender is widely cultivated around the world, and L angustifolia is the most common species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the possession of antibacterial and anti-cancer activities, plant essential oil has become the focus of phytomedicine research 40 , 41 and drug delivery system formulation development. 42 In recent times, lavender is widely cultivated around the world, and L angustifolia is the most common species.…”
Section: Discussionmentioning
confidence: 99%
“…1,37,38 The effects of green tea polyphenols for prostate cancer prevention and treatment have been studied in epidemiological, preclinical, and early clinical investigations. 39 Owing to the possession of antibacterial and anti-cancer activities, plant essential oil has become the focus of phytomedicine research 40,41 and drug delivery system formulation development. 42 In recent times, lavender is widely cultivated around the world, and L angustifolia is the most common species.…”
Section: Discussionmentioning
confidence: 99%
“…ducts and vittae) occurring in the vegetative and reproductive organs. [4] Recently, these essential oils are gaining an increasing interest as effective and eco-friendly biopesticides, [5 -7] as well as antiprotozoal, [2] [8] antimicrobial, [9] and anticancer [10] [11] agents. Among the major constituents of the Apiaceae essential oils, monoterpenes, sesquiterpenes, and phenylpropanoids are the most common.…”
Section: Introductionmentioning
confidence: 99%
“…[4] However, many phytochemicals including essential plant oils have shown their benefits in various cancer cell lines. [25] The authors observed MN frequencies in exfoliated buccal cells in normal mucosa, precancerous lesions and squamous cell carcinoma of Indian participants and concluded that the MN frequency may be a marker of epithelial carcinogenic progression. [26] Here, we have focused on the MN formation, apoptosis frequency and detection of chromosomal abnormalities and observed in various cases of premalignant and malignant stages of OSCC and their association with various risk factors in participants of West Bengal, which will help us to analyze the extent of carcinogenic invasion and compare these with the control groups.…”
Section: Discussionmentioning
confidence: 99%